Young Women's Readiness for Menarche - Desta Rini Aftania; Yuyun Setyorini; Sunarsih Rahayu (JENDELA NURSING JOURNAL, 2022)
Background: eighteen percent or 1.2 billion people of the world's population are in their teens. A common problem that is often experienced by pre  pubertal teenage girls in preparing for puberty is the lack of exposure to information. Health education is one of the efforts to prepare young women to be ready to face menarche. Based on a preliminary study conducted with BKKBN officers and Genre Ambassadors of Pacitan Regency, he said that young women need a lot of preparation and information to face menarche. Meanwhile, based on a pre liminary study conducted on students in grades IV, V, and VI at Bangunsari State Elementary School, it was found that the majority of students had never received information about menstruation.Purpose: to determine the effect of health education on the readiness of young women to face menarche.Methods: this type of research is quantitative experimental research, using a pre experimental research design with one group pre-post test design. The sampling technique used, namely purposive sampling, a total of 41 respondents. The research instrument used a questionnaire sheet. Statistical test using Wilcoxon test.Results: the results of the Wilcoxon pre-test and post-test knowledge and attitudes of 41 respondents showed a p-value of 0.000, which means that there is an effect of health education on young women's readiness to face menarche.Conclusion: there is an effect of health education on the readiness of young women to face menarche.